Safety and efficacy of histotripsy delivery through overlying gas-filled small bowel in an ex vivo swine model - Meridith A. Kisting; James K. White; Sarvesh Periyasamy; Ayca Z. Kutlu; Adrienne L. Kisting; Xiaofei Zhang; Lu Mao; Paul F. Laeseke; Martin G. Wagner; Eli Vlaisavljevich; Fred T. Lee; Timothy J. Ziemlewicz (International Journal of Hyperthermia)
Purpose To evaluate the safety and efficacy of performing histotripsy through overlying gas-filled bowel in an ex vivo swine model.Methods An ex vivo model was created to simulate histotripsy treatment of solid organs through gas-filled bowel. Spherical 2.5 cm histotripsy treatments were performed in agar phantoms for each of five treatment groups: 1) control with no overlying bowel (n = 6), 2) bowel 0 cm above phantom (n = 6), 3) bowel 1 cm above phantom (n = 6), 4) bowel 2 cm above phantom (n = 6), and 5) bowel 0 cm above the phantom with increased treatment amplitude (n = 6). Bowel was inspected for gross and microscopic damage, and treatment zones were measured. A ray-tracing simulation estimated the percentage of therapeutic beam path blockage by bowel in each scenario.Results All histotripsy treatments through partial blockage were successful (24/24). No visible or microscopic damage was observed to intervening bowel. Partial blockage resulted in a small increase in treatment volume compared to controls (p = 0.002 and p = 0.036 for groups with bowel 0 cm above the phantom, p > 0.3 for bowel 1 cm and 2 cm above the phantom). Gas-filled bowel was estimated to have blocked 49.6%, 35.0%, and 27.3% of the therapeutic beam at 0, 1, and 2 cm, respectively.Conclusion Histotripsy has the potential to be applied through partial gas blockage of the therapeutic beam path, as shown by this ex vivo small bowel model. Further work in an in vivo survival model appears indicated.